Analisis Kebutuhan Media Pembelajaran IPA Berbasis 4C untuk Penguatan Keterampilan Abad 21 di SMP Negeri 20 Lebong - Astuti, Asmi; Fitriani, Apriza (Mahesa Research Center, 2025)
The demands of 21st-century education emphasize the development of 4C skills (Critical Thinking, Creativity, Communication, Collaboration). However, science learning at SMP Negeri 20 Lebong has not been optimal in implementing innovative digital media that support these skills. Therefore, this study aims to analyze the need for developing 4C-based science learning media to improve students' 21st-century skills at the school. The method used was a descriptive quantitative survey-based method, involving 105 students in grades VII, VIII, and IX. Data were analyzed using descriptive statistics. The results indicate an urgent need for innovation. 87.1% of students require alternative learning methods, and 58.1% of students still have difficulty understanding abstract science material, especially the Coordination, Reproduction, and Pressure Systems, triggered by the many formulas and concepts. The majority of students (76.3%) consider the available media inadequate, and 82.8% require additional media, with 96.8% wanting digital technology-based media (computers/laptops/smartphones). Only 49.5% of students feel that teachers have encouraged critical thinking in learning. These findings provide a strong foundation for the development of 4C-based interactive science learning media that is digitally and collaboratively oriented, which concretely contributes to visualizing abstract concepts, increasing engagement, and strengthening students' 21st-century competencies.